Effects of surface texture on wetting - Fong, Veronica Cheng Xi (2019)
The degree of wetting is determined by measuring the contact angle formed between the liquid and solid surface. It can be enhanced through several methodologies such as chemical alteration and changing the surface topography. By doing so, the interfacial interactions among the three phases of matter can be modified. In this project, the alteration of the surface topography method will be used to investigate the degree of wetting. Fabrication of circular and square shaped micropillars through photolithography technique will be placed atop the surfaces to simulate different surface topographies. The advantage includes being able to study the effects of wetting in a controlled manner by using the theoretical approaches in this field. Circular shaped micropillars were known to display better results in terms of degree of wetting as compared to square shaped micropillars. Wettability enhancement with spray coating was also evident in this experiment which gives rise to the effectiveness of the spray coating method. By keeping the correlations of the roughness factor and top surface ratio in mind, the best results have been exhibited by the largest spacing distance with the circular micropillars. Therefore, a comprehensive analysis of surface topography alteration through micropillars and comparison with the spray coating method will be given.